Detection of early phenotype cardiac sarcoidosis by cardiovascular magnetic resonance. Issue 5 (September 2021) - Levin, Benjamin; Baughman, Robert P.; Sweiss, Nadera J.
Abstract : Purpose of review: Cardiac sarcoidosis has high prevalence in sarcoidosis patients and contributes to significant morbidity and mortality. Early detection of cardiac sarcoidosis is essential to improving patients' symptoms and cardiovascular outcomes. Recent findings: Cardiovascular magnetic resonance imaging (CMR) is an excellent diagnostic modality for cardiac sarcoidosis. However, early phenotypes of cardiac sarcoidosis have more mild imaging phenotypes. These mild and sometimes subtle imaging phenotypes of cardiac sarcoidosis have lower diagnostic sensitivity and specificity for cardiac sarcoidosis by CMR when compared with more severe imaging phenotypes of cardiac sarcoidosis. In addition, many sarcoidosis patient cohorts frequently have heterogenous potential alternative etiologies for mild myocardial disease detected by mild late gadolinium enhancement (LGE) findings. In early phenotype cardiac sarcoidosis, analysis of the LGE pattern and location can improve the diagnostic specificity of these mild LGE findings. Summary: The current review focuses on the current strengths and challenges in CMR detection of early phenotypes of cardiac sarcoidosis by the LGE technique.